PEMBUATAN DAN KARAKTERISASI PLAFON DARI SERBUK AMPAS TEBU DENGAN PEREKAT POLIESTER - rizki winda sari (Saintia Fisika, 2013)
Studies of plafon have been made with using bagasse. Studies have been done to know the best combination of bagasse powder and polyester with composition of variations to 4 : 8 gr, 6 : 8 gr, 8 : 8 gr, 10 : 8 gr, and 12 : 8 gr. The properties of plafon that analyzed to test physical properties such as water absorption, density and mechanical properties including impact test, the tensile test and bending strength test. The results show that the physical properties (density 1,41gr/cm3 and water absorption 11,54 %) on the composition of bagasse at 4 gr powder are the best results. The higher levels of bagasse powder water absorption the higher the value, so as lower density uptake. Physical properties test results still complete the standards of ISO 03-2105, 1996. From testing the mechanical properties (the tensile test 3058,6 kPa and bending strength test 17,01 MPa and impact test 2 kJ/m2). From all the best specimens test, the composition of 8:8 the best mechanical properties, the results of physical properties also still complete the standards of ISO 03-2105, 1996, so that the composition of 8:8 can be used as a plafon